Porous beta titanium alloy coated with a therapeutic biopolymeric composite to improve tribomechanical and biofunctional balance - Ernesto J., Delgado-Pujol (2023)
Tooth loss is common in patients struggling with dental cavities, periodontal diseases, and tumors, as well as those who abuse tobacco or drugs. In this scenario, dental implants have become the primary treatment option for complete or partial tooth loss. Dental implant failure can be caused by stress shielding phenomenon, poor osseointegration, or to bacterial infections. In the present study, a joint solution to these limitations is proposed using a variety of porous β-titanium substrates using powder Ti35Nb7Zr5Ta alloy and employing the spacer-holder approach (ammonium bicarbonate) to obtain a variety of porosity percentage (30, 40, and 50 vol%), and pore diameters in 100–200 μm, that has been characterized in terms of its size distribution, density, morphology, chemical composition, compaction ability and Vickers micro-hardness. Furthermore, porosity, microstructure (Archimedes and image analysis) and tribomechanical behavior (P-h curves and scratch tests) experiments were performed to study and characterize the porous substrates. Polyvinyl alcohol (PVA)/poly-ε-caprolactone (PCL) containing silver nanoparticles (AgNPs), as antibacterial composite, was employed to infiltrate β-Ti disks. Scanning electron microscopy was used to determine the coating morphology, thickness, and infiltration of the porous substrates. Wettability and SBF experiments were also carried out to investigate hydrophobicity and potential bio-functionality. The results suggested how the porosity of the β-Ti alloy affects the mechanical characteristics and the wettability of the substrate that was successfully infiltrated to exert an antimicrobial behavior.